2021
DOI: 10.1177/13623613211007717
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder prevalence and associated sociodemographic factors in the school population: EPINED study

Abstract: The autism spectrum disorder prevalence data for southern Europe seem to be lower than international reports. The objective of the Neurodevelopmental Disorders Epidemiological Research Project was to estimate the prevalence of autism spectrum disorder in a representative school sample of Tarragona, Spain. Screening was performed through parents ( N = 3727) and teachers ( N = 6894), and 781 children were individually assessed. The overall estimated prevalence was 1.53% (1.78% in preschoolers; 1.30% in primary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 78 publications
0
10
0
1
Order By: Relevance
“… 50 According to recent estimates, more than 70 million people worldwide have suffered from autism, and the overall estimated prevalence is between 1.5% and 2%. 51 , 52 Modifications in diagnostic criteria and increased awareness of autism in people might be responsible for the surge in autism. Estimates of autism prevalence in different populations and settings vary by definition, sampling, and assessment of independent population cases among studies.…”
Section: Clinical Overview and Genetic Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“… 50 According to recent estimates, more than 70 million people worldwide have suffered from autism, and the overall estimated prevalence is between 1.5% and 2%. 51 , 52 Modifications in diagnostic criteria and increased awareness of autism in people might be responsible for the surge in autism. Estimates of autism prevalence in different populations and settings vary by definition, sampling, and assessment of independent population cases among studies.…”
Section: Clinical Overview and Genetic Featuresmentioning
confidence: 99%
“…Notably, there is a prominent sex difference in the prevalence of ASD, with prevalences of 2.8% in males and 0.65% in females and a male-to-female ratio of 4.3:1. 51 , 52 This suggests that unknown biological factors may play a role. 53 56 Moreover, a recent study showed an increased female-to-male odds ratio for ASD comorbidities and showed that comorbidity occurrence was associated with the age at first autism diagnosis.…”
Section: Clinical Overview and Genetic Featuresmentioning
confidence: 99%
“…The difference between these regions is explained by varying amounts of published epidemiological studies concerning the problem. Within the last decade, the incidence of ASD diagnoses has increased by 0.7% (before: 0.83%, currently: 1.53%) [ 10 ]. The disorder is more frequently found among boys than girls (4.4:1 ratio) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…ASD includes various neurodevelopmental disorders with diverse etiologies such as Autistic Disorder, Pervasive Developmental Disorder not Otherwise Specified (PDD-NOS), and Asperger’s Disorder. The overall estimated prevalence of ASD ranges from 1.5% to 1.8% and an increase has been reported around the world over the past decade [ 3 , 4 ]. Males show a prevalence of 2.8% and females a prevalence of 0.65%, making the male-to-female ratio of 4.3:1 [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The overall estimated prevalence of ASD ranges from 1.5% to 1.8% and an increase has been reported around the world over the past decade [ 3 , 4 ]. Males show a prevalence of 2.8% and females a prevalence of 0.65%, making the male-to-female ratio of 4.3:1 [ 3 , 4 ]. A combination of genetic, environmental and immunological factors underlie ASD [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%